Adherent‐invasive Escherichia coli (AIEC): Cause or consequence of inflammation, dysbiosis, and rupture of cellular joints in patients with IBD?. Issue 6 (3rd January 2020) - Perna, Angelica; Hay, Eleonora; Contieri, Marcella; De Luca, Antonio; Guerra, Germano; Lucariello, Angela
Abstract: There are many factors contributing to the development of gastrointestinal diseases, grouped into genetic, environmental, and lifestyle factors. In recent years attention has fallen on pathogens; in particular, Bacteroides fragilis, Fusobacterium nucleatum, Escherichia coli ( E. coli ) and Helicobacter pylori have been studied. Several points remain to be clarified, and above all, as regards the adherent‐invasive E. coli strains of E. coli, one wonders if they are a cause or a consequence of the disease. In this review, we have tried to clarify some points by examining a series of recent publications regarding the involvement of the bacterium in the pathology, even if other studies are necessary. Abstract : There are many factors contributing to the development of gastrointestinal diseases, grouped into genetic, environmental, and lifestyle factors. Several studies have tried to clarify whether there could be an association between some bacterial strains and the development of irritable bowel syndrome, in particular, if the adherent‐invasive Escherichia coli strain is responsible for the development of the pathology.